Design Low Noise Voltage Amplifier for Hand-Held Electronic Reader. Issue 1 (May 2020) - Afnan Uda, M.N.; Bahari Jambek, Asral; Hashim, U.; Uda, M.N.A.
Abstract: There are limited number of electrical based two type electrode electronic readers for biosensors are commercial available because of the noise issues and amplification at nano to pico ampere current range. This research is mainly focused on designing an active low pass filter circuit of electronic reader for biosensors. The entire circuits are comprised of a voltage converter circuit, active low pass filter circuit, voltage amplifier, microcontroller and display unit. The circuit capture, filter and amplify nano and pico ampere current convert it to detectable voltage range as an output signal to the processing circuit. NodeMCU was act as the process and control circuit to read the output voltage from the amplifier circuit. The signal generator will act as a replacement for the biosensor input current and oscilloscope will display the input and output signal. The Design Spark PCB software was used to design the voltage amplifier circuit. Arduino software was used to create a programming code to upload in NodeMCU microcontroller.